Development of subject-oriented innovative software products based on artificial intelligence systems - О. Стенін; В. Пасько; О. Лісовиченко; О. Польшакова; В. Солдатов (Adaptivni Sistemi Avtomatičnogo Upravlinnâ)
It is known that knowledge about the object being developed, in this case an innovative software product, determines the structure of the management system for its development. This is true for the control system for the development of most objects of different physical nature and their purpose. However, software products have an important feature: knowledge about them has a relatively large dynamic component, so large that it often needs to be taken into account even in operational management. A high level of validity of innovative solutions in the process of managing the development of an innovative software product can`not be achieved without the strong cognitive ability of the developer in relation to the software product. This is due to the evolution of knowledge in the subject area. This article proposes an infological model of the process of managing the development of an innovative software product. The essence of the proposed approach is that the development of an innovative software product is interpreted as an information object that is meaningfully and structurally changes in the process of its creation. The structure of an intelligent decision support system is proposed, which allows making innovative decisions at each stage of the process of developing an innovative software product.